Parody: Dimensions and Pespectives. Edited, with an introduction, a bibliography, and an index by Beate Müller. Rodopi Perspectives on Modern Literature, Amsterdam - Atlanta, GA 1997, 313p. - Siaflékis, Z. (Σύγκριση/Comparaison/Comparison, 2017)
No abstract availabe